All‐in‐One Theranostic Platform Based on Hollow Microcapsules for Intragastric‐Targeting Antiulcer Drug Delivery, CT Imaging, and Synergistically Healing Gastric Ulcer. Issue 9 (8th February 2022) - Wang, Qi; Xu, Yu; Xue, Rui; Fan, Jingmin; Yu, Hang; Guan, Jiawei; Wang, Hongzheng; Li, Min; Yu, Wei; Xie, Zhiyong; Qi, Rong; Jia, Xin; et al.
Abstract: Bismuth‐containing therapies are suggested as first‐line and rescue alternatives for gastric ulcer (GU) treatment and Helicobacter pylori eradication. The current treatment strategy is called quadruple therapy and includes proton pump inhibitors, bismuth, and two broad‐band antibiotics. This fact may affect medication compliance, leading to a resistance rate of more than 25% to clarithromycin or metronidazole. To counter this, from the perspective of natural products, an intragastric‐targeting all‐in‐one theranostic platform is established: a drug carrier microcapsule composed of multiple synergistic antiulcer drugs, including bismuth, gallotannin, and antibiotics is obtained (BiG@MCs), and the therapeutic effects of BiG@MCs in rodent models are further evaluated. The results show that the BiG@MCs are spherical with homogeneous particle size (3 ± 0.5 µm) and can be response‐released to the acidic environment of the stomach (pH 2.0–3.0), preventing the premature release of the BiG@MCs in physiological conditions. It is worth noting that the bismuth component can be easily identified by computed tomography and other detection instruments, which provide the possibility for drug tracing. In summary, these results indicate that BiG@MCs provide a versatile intragastric‐targeting drug delivery platform for GU therapeutics. Abstract : Bismuth ions and natural polyphenols are coordinated into a metal phenolic network (MPN). Tetracycline is used as a model drug to evaluate the efficacy and drug carrying capacity of the MPN. The results show that the drug delivery system constructed in this work provides a versatile intragastric‐targeting all‐in‐one theranostic drug delivery platform for gastric ulcer therapeutics.